Megathopa villosa (Coleoptera, Scarabaeidae, Scarabaeinae): first distributional records for the Chilean transitional coastal desert - ALFARO, FERMÍN M.; PIZARRO-ARAYA, JAIME; MONDACA, JOSÉ (Revista Colombiana de Entomología, 2008)
Megathopa villosa (Coleoptera, Scarabaeidae, Scarabaeinae) is reported for the first time in the coastal transitional desert of Chile. Specimens of this species were captured in several coastal localities in the northern part of the country. The captures were made at night using white-light traps. A brief description is provided of the habitat where the specimens were collected, along with a diagnosis of the species.